Evaluation of the solar heat gain coefficient of innovative aerogel glazing systems: Experimental campaigns and numerical results. (15th December 2022) - Hassani, A.R.; Domenighini, P.; Belloni, E.; Ihara, T.; Buratti, C.
Abstract: Solar Heat Gain Coefficient (SHGC) has a significant impact on heating and cooling loads throughout transparent and translucent building elements. Very few studies dealing with the estimation of SHGC are available in the literature for innovative highly insulating solutions, such as aerogel-based windows, and data in general lack accuracy and are based on inaccurate optical information. The present paper proposes a new analytical model aiming at calculating the solar factor of innovative granular aerogel-filled glazing systems. A dynamic heat transfer model, based on the energy balance equation, was developed and solved in the Simulink/Matlab environment. An experimental field set up at pilot scale was also used in order to try to validate the simulation model. Two aerogel-based glazing solutions (AGS1 and AGS2), different for the camera filling, and a standard glazing system (SGS) were installed and monitored under real climatic conditions in October 2020, January 2021, and September 2021. During the experimental campaigns, the SHGC of the three solutions was calculated, by using a simplified equation based on laboratory scale characterization of the samples and on temperatures and solar radiation measured in situ. The SHGC of the three samples was evaluated by means of simulations (SM) and field measurement (FM) procedure and compared with estimated values, when available. Both experimental and simulation results for SGS are in very good agreement with the actual SHGC value, allowing a validation of the simulation model and of the experimental approach (maximum differences in the 1–3% range). For AGS1, SM results are closer than the experimental data to the value estimated with EN 410:2011. For AGS2, a comparison with the reference standard was not possible because the method could not be applied. In general, the values obtained for the SM method are higher than the ones of FM one, with differences in the 22–28% range. The disagreement could be related to the surface temperatures measured on the glazing panes, which are not very reliable in an experimental field. However, the SM method seems to be more suitable because less influenced by the weather conditions. Highlights: New analytical model for calculating solar factor of granular aerogel glazing systems. Dynamic heat transfer model developed in Simulink/Matlab environment. Experimental field set up at a pilot scale for the model validation. Satisfactory agreement between some experimental and simulated data.